Prevalence and genetic diversity of norovirus infection in Tunisian children (2007–2010). Issue 6 (26th March 2013) - Hassine‐Zaafrane, Mouna; Sdiri‐Loulizi, Khira; Kaplon, Jérôme; Salem, Imen Ben; Pothier, Pierre; Aouni, Mahjoub; Ambert‐Balay, Katia
Abstract: Viral gastroenteritis can be a life‐threatening disease in infants and young children, especially in developing countries. The aim of this study was to continue the epidemiological surveillance of norovirus (NoV) infections in Tunisian children suffering from acute gastroenteritis. Surveillance was initiated in January 2003, to monitor potential variations in strains over time, in terms of frequency and diversity of NoV genotypes, and more particularly the potential emergence of new GII.4 variants following the 2004 Hunter variant. From April 2007 to April 2010, a total of 407 stool specimens were collected from sporadic cases (238 inpatients and 169 outpatients). Furthermore, 28 stool samples were collected from children involved in 3 gastroenteritis outbreaks. Stool specimens were screened for NoV genogroup I (GI) and II (GII) by RT‐PCR. NoV strains were genotyped, and variants identified, based on sequence and phylogenetic analyses of the polymerase and capsid genes. NoVs were detected in 38 sporadic cases (9.3%) and 21 epidemic cases (75%). Great diversity was observed throughout the period, with seven distinct NoV genotypes characterized in sporadic cases, and three in outbreaks. GIIb/II.3 and GII.4 were predominant globally, with fluctuations of their prevalence over time. Interestingly, the Hunter variant, which was the unique GII.4 variant observed from 2003 to April 2007 in the region of Monastir, was replaced by the 2006b variant. NoV is an important enteropathogen responsible for viral gastroenteritis among infants and children in Tunisia, and the infecting strains between 2007 and 2010 were different from those in previous years. J. Med. Virol. 85: 1100–1110, 2013. © 2013 Wiley Periodicals, Inc.